Biogeography of a plant invasion: genetic variation and plasticity in latitudinal clines for traits related to herbivory. Issue 1 (16th November 2016) - Bhattarai, Ganesh P.; Meyerson, Laura A.; Anderson, Jack; Cummings, David; Allen, Warwick J.; Cronin, James T.
Abstract: The juxtaposition of plant‐species invasions with latitudinal gradients in herbivore pressure is an important yet mostly unexplored issue in invasion biology. Latitudinal clines in defense and palatability to herbivores are expected to exist in native plant species but the evolution of these clines may lag behind for invasive plant species resulting in non‐parallel latitudinal clines that may impact invasion success. Our study focused on a native and European invasive lineages of the common reed Phragmites australis in North America. Using native and invasive genotypes of P. australis collected across a 17° latitudinal range, we performed experiments in replicate northern and southern common gardens to investigate whether these two lineages exhibited different genetically based latitudinal clines in defenses, nutritional condition, and palatability to their herbivores, the aphid Hyalopterus pruni and the fall armyworm Spodoptera frugiperda . We also tested whether invasive genotypes are more phenotypically plastic than native genotypes and whether plasticity varies with latitude. Although invasive genotypes did not exhibit higher defense levels (leaf toughness, phenolics, percent carbon), they were considerably less palatable to their herbivores than native genotypes. Genetically based latitudinal clines were evident for both native and invasive P. australis and for all defenses, nutrients, and at least one palatability trait for each herbivore. In 36% of the cases where clines were evident, they were non‐parallel between the two lineages. These data suggest that clines in the invasive genotypes of P. australis evolved within the past 100 years. Moreover, our study showed that the occurrence and direction of latitudinal clines in plant traits were commonly dependent on where the study was conducted (north or south), indicating strong phenotypic plasticity in these genetic‐based clines. Finally, traits for invasive genotypes of P. australis were 2.5 times more plastic than traits for native genotypes. Interestingly, plasticity for native but not invasive genotypes was strongly dependent on latitude of origin. Such spatial heterogeneity within and between the native and invasive lineages of P. australis with respect to their interactions with herbivores can generate substantial spatial variability in biotic resistance that can have important implications for the establishment and spread of invasive genotypes and species.